Learning Difficulty Analysis of Improvement Student Achievements in The Pandemi of Covid 19 Class VII SMP PGRI 03 Paga District Paga Sikka District - Muna, Fitrianti; Kasim, Abdul Muis; Nuwa, Gisela (Jurnal Riset Ilmu Pendidikan, 2023)
This study aims to find out the difficulties that affect the learning process on the achievement of class VII students during the Covid-19 pandemic and to find out how to overcome learning difficulties for class VII students through online during the Covid-19 pandemic at SMP PGRI 03 Paga. This research was carried out for one month, starting from August 10 to September 10 2021. The research method used was a descriptive method with a qualitative approach. Data collection techniques through observation, interviews and process on student achievement, namely some students do not have facilities or cellphones to access online learning due to the poor condition of students. Therefore, the results of this study can be concluded that there are difficulties that affect the learning process on student achievement so that some students do not undersand about online learning applications and also do not understand the material delivered through the online learning process.